Early Jurassic Trigoniida (Bivalvia) from Argentina. (December 2021) - Echevarría, Javier; Damborenea, Susana E.; Manceñido, Miguel O.
Abstract: Bivalves of the Order Trigoniida were abundant and diverse in the Andean Early Jurassic shallow-marine paleoenvironments. Based on extensive collections with detailed stratigraphic information from 40 localities in central-western Argentina, we describe 20 species (4 new) belonging to 11 genera (3 new) and 5 families (Groeberellidae, Trigoniidae, Prosogyrotrigoniidae, Frenguelliellidae, and Myophorellidae). The abundant material allows the description of ontogenetic development and intraspecific variability, highlighting the likely phylogenetic significance of previously underestimated features. Within Frenguelliellidae, we show that the stratigraphic range of Frenguelliella Leanza in the region is restricted to the Sinemurian–Pliensbachian. We propose Poultoniella new genus for some late Pliensbachian–Toarcian species. Jaworskiella Leanza is limited to its type species, whereas for certain convergent forms we propose Moerickella new genus (most likely the oldest Myophorellidae). Pseudovaugonia new genus likely descended from Moerickella n. gen., rather than from the highly diverse Promyophorella Kobayashi and Tamura, and is unrelated to Vaugonia Crickmay. Frenguelliella chubutensis (Feruglio) and Promyophorella basoaltorum new species are the most frequently occurring species. Some species were probably endemic (e.g., Promyophorella ? sanjuanina new species), although a few (such as Frenguelliella eopacifica new species and Poultoniella jaworskii new genus new species) had a wide paleolatitudinal range and occur throughout the Pacific coasts and terranes of the Americas, revealing a significant faunal interchange among marine basins during Hettangian–Pliensbachian times. The well-documented Argentinian Early Jurassic record shows a rapid recovery and radiation of the Trigoniida after the Triassic/Jurassic extinction. Many of the new taxa that evolved in America eventually dispersed worldwide by Toarcian and Middle Jurassic times. UUID: http://zoobank.org/82c0d95e-f147-4736-a417-ebc252911181 .